2014
DOI: 10.1111/jsap.12212
|View full text |Cite
|
Sign up to set email alerts
|

Transrectal bladder prolapse secondary to pelvic fracture in two dogs

Abstract: This report describes the exteriorisation of the urinary bladder in two dogs as a result of a laceration of the rectum from a traumatic pelvic fracture. Clinical examination and contrast radiography of the bladder were used as diagnostic tools. Both patients were treated with exploratory laparotomy, where traction of the bladder was utilised to pull the bladder through the traumatic rectal laceration allowing the organ to return to its normal anatomical position. This procedure was followed by surgical reconst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…A review of the medical literature has identified a single report of transanal bladder prolapse due to pelvic fracture occurring in two dogs. 4 …”
Section: Discussionmentioning
confidence: 99%
“…A review of the medical literature has identified a single report of transanal bladder prolapse due to pelvic fracture occurring in two dogs. 4 …”
Section: Discussionmentioning
confidence: 99%